Development and evaluation of a catalytic stripper for the measurement of solid ultrafine particle emissions from internal combustion engines. Issue 6 (2nd June 2020) - Melas, A. D.; Koidi, V.; Deloglou, D.; Daskalos, E.; Zarvalis, D.; Papaioannou, E.; Konstandopoulos, A. G.
Abstract: Solid particle number vehicle exhaust measurements necessitate an aerosol conditioning system that removes efficiently volatile particles, does not create artifacts, and minimizes solid nucleation particle losses. Here, we present the development and evaluation of a catalytic stripper (CS) based on a unique dual-function monolithic reactor that oxidizes hydrocarbons and stores sulfur material. The CS was tested for its tetracontane particle removal efficiency, sulfur adsorption capacity with sulfur dioxide, and particle penetration with solid CAST-generated particles. The optimal operation conditions were examined including different aerosol flows and configurations, i.e., as a stand-alone device and as part of a volatile removal system with a hot and a cold dilution stage upstream and downstream of the CS, respectively. The CS managed to comply with current legislation requirements for solid particle number measurements down to 23 nm as a stand-alone device and showed great potential as part of a volatile particle removal (VPR) system for measurements at least down to 10 nm. Finally, we compared the performance of two VPR systems that use the developed CS (VPR-CS) and an evaporation tube (VPR-ET), respectively. Our results suggest that the VPR-CS exhibits higher volatile removal efficiency without creating artifacts while the particle losses are lower with the VPR-ET. Nevertheless, when measuring solid nucleation particles generated by a diesel engine with the VPR-CS, the measurement uncertainty was very low due to its high particle penetration fractions.